THE MAIN STAGES OG THE FORMATION OF THE INTERNATIONAL LEGAL MECHANIZM FOR THE REGULATION OF DIRECT TELEVISION BROADCASTING - Волошко, Ю. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The process of formation of the international legal mechanism of regulation of direct television broadcasting is analyzed. Three stages of development of such mechanism are allocated. The focus is on the third phase, which is characterized by an increasingly close relationship with the private sector and a change in the approach to the provision of live television services. The main problems and trends of this sphere of legal relations are highlighted.